Hubungan Berat Badan Lahir Rendah Dengan Kejadian Stunting di Wilayah Kerja Puskesmas Sawan I: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2020)
Introduction: The problem of stunting has a big impact on the generation and development of the nation. Studies on the factors that increase the prevalence of stunting are still mixed. The high incidence of low birth weight (LBW) is thought to be the cause of the high incidence of stunting. This study aims to determine the relationship between low birth weight and the incidence of stunting. Methods: This study is an analytical study with a cross sectional design and uses secondary data. The data were taken from the Posyandu information system records in 2020 in the Sawan I Community Health Center. Data were analyzed using Chi Square analysis. Results: Most of the children under five who were born with LBW were stunted (17.8%), and those who were born normally or not LBW were not stunted (71.2%). Based on the Chi Square statistical test at the 95% confidence rate, the p value is 0.01 <0.05 so that Ho is rejected and Ha is accepted, which means that there is a relationship between low birth weight and the incidence of stunting in children under five. Conclusion: there is a relationship between low birth weight and the incidence of stunting in children under five in the Sawan I Health Center. Key words: stunting, low birth weight, children under five